2019
DOI: 10.1111/tmi.13241
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluations of onchocerciasis interventions: a systematic review and research needs

Abstract: Objective To provide a systematic review of economic evaluations that has been conducted for onchocerciasis interventions, to summarise current key knowledge and to identify research gaps. Method A systematic review of the literature was conducted on the 8th of August 2018 using the PubMed ( MEDLINE ) and ISI Web of Science electronic databases. No date or language stipulations were applied to the searches. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 125 publications
(221 reference statements)
0
27
0
Order By: Relevance
“…An overview of the studies is presented in Table 1. Interestingly, there were notably more economic evaluations of schistosomiasis than those identified in previous reviews for other helminth infections of human health importance [15][16][17] .…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…An overview of the studies is presented in Table 1. Interestingly, there were notably more economic evaluations of schistosomiasis than those identified in previous reviews for other helminth infections of human health importance [15][16][17] .…”
Section: Resultsmentioning
confidence: 97%
“…The costs of preventive chemotherapy vary across different settings [15][16][17] , both within and between countries. A driver is the size of the targeted population 120-122 .…”
Section: Preventive Chemotherapy Cost Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, controlling and eliminating onchocerciasis with enhanced onchocerciasis elimination plans are highly desirable. Economic evaluations of onchocerciasis interventions have been favorable …”
Section: Treatmentmentioning
confidence: 99%
“…Increased cost-benefit of strengthening onchocerciasis elimination efforts in areas with high onchocerciasis-associated epilepsy Turner et al [1], in their excellent systematic review of economic evaluations of onchocerciasis interventions, estimated the cost per disability-adjusted life year (DALY) averted by annual ivermectin distribution as between US $3 and US $30. Based on these studies, a very little additional benefit was demonstrated with biannual compared to annual ivermectin distribution (only a 3-4% increase in the number of DALY averted, while the cost will increase by 50-60%).…”
Section: Letter To the Editormentioning
confidence: 99%